PREVALENCE OF METABOLIC SYNDROME AMONG APPARENTLY HEALTHY WORKFORCE - Roomi, Mudassar Ali; Mohammadnezhad, Masoud (Journal of Ayub Medical College Abbottabad, 2019)
Metabolic syndrome (MetS) is clustering of various cardiometabolic risk factors and it increases the risk of cardiovascular diseases and diabetes. Unhealthy lifestyle predisposes employees to increased risk of MetS. This systematic review was conducted to investigate the prevalence of MetS and its associated factors among working population. Studies published in English during 2005-2017 on the prevalence of MetS in workforce were searched. MetS was defined using Adult Treatment Panel-III criteria and searches were carried out in various databases using keywords for titles and/or abstracts. Forty articles, containing 435,013 participants aged 38.5 (18-64) years, were finally included. Overall average prevalence of MetS was 21.7% (6.1-58%). Average prevalence of MetS was higher in males (21.9%) than in females (14.1%). Region-wise prevalence of MetS was 27.93% in North America, 27.65% in South America, 21.27% in Asia, 16.04% in Africa, and 10.47% in Europe. Mean prevalence of each component of MetS was 39.1% for low HDL, 33.7% for hypertension, 30.8% for hypertriglyceridemia, 29.2% for central obesity, and 17.6% for hyperglycemia. Major factors associated with MetS were male gender, aging, inactivity, smoking, stress, elevated liver enzymes, higher education, longer work experience, alcohol abuse, shift work, and lower fruit intake. Prevalence of MetS among workforce was high and it decreases work performance and increases personal and corporate health-care cost. Employees are suggested to enhance physical activity and adopt healthy lifestyle. Employers may increase the cardiometabolic health of their employees by increasing awareness, routine screening for MetS, and by providing various health promotion programs at the worksite. Keywords: Cardiometabolic risk; metabolic syndrome; obesity; occupational health